Remifentanil and propofol undergo separation and layering when mixed in the same syringe for total intravenous anesthesia. Issue 7 (5th May 2016) - O'Connor, Sean; Zhang, Yan Ling; Christians, Uwe; Morrison, John E.; Friesen, Robert H.
Summary: Background: Propofol and remifentanil can be combined to deliver total intravenous anesthesia (TIVA). Propofol and remifentanil are sometimes mixed in the same syringe. Since remifentanil is a solution and propofol is an emulsion, we hypothesized that they would separate over time when mixed in the same syringe. Methods: Nine 60‐ml polypropylene syringes were prepared as follows: Group A: 1.25 ml of remifentanil solution (1 mg·ml −1 ) was added to 48.75 ml of propofol (10 mg·ml −1 ) in three syringes. Group B: 2.5 ml of remifentanil (1 mg·ml −1 ) was added to 47.5 ml of propofol (10 mg·ml −1 ) in three syringes. Group C: 5 ml of remifentanil (1 mg·ml −1 ) was added to 45 ml of propofol (10 mg·ml −1 ) in three syringes. The remifentanil lyophilized powder was reconstituted with sterile water and added to the propofol by injection through the port on the bottom of the syringe. The syringe was then inverted five times in succession to mix the drugs. The syringes were mounted in an upright vertical position (plunger on top, port on bottom) with wire on a pegboard. Samples of the mixture were taken from the bottom port (via a 3‐way stopcock) and from the top of the syringe (via a stopcock on an 18‐gauge needle placed 5 mm through the plunger) at the following time intervals (min) from baseline: T0, T10, T30, T60, T120, T180, T240, T300. Remifentanil and propofol were quantified using specific and validated HPLC/MS/MS assays with automated online sample preparation. Results: Concentrations of remifentanil were significantly greater at the top than the bottom of the syringes in groups A and B. Concentrations of propofol were significantly greater at the bottom than the top of the syringes in all groups. Conclusion: Our data indicate that remifentanil solution and propofol emulsion are immiscible: remifentanil separates from propofol and rises to the top. Thus, concentrations of remifentanil and propofol delivered to patients from the same syringe during TIVA are not those expected and cannot be reliable. Remifentanil and propofol should be administered in separate syringes when used in combination for TIVA. Abstract :